PEMANFAATAN LIMBAH KUBIS MELALUI FERMENTASI SEBAGAI PENGOLAHAN PAKAN ALTERNATIF UNTUK AYAM KAMPUNG: PENGALAMAN KKN-PMM DESA KALIKUNING - Tugiyanti, Elly; Hartini, Sri; Oktasari, Sully Kemala; Mustika Sari, Astri; Rohma, Rina Aulia; Mushaddaq, Almaas Fakhri; Azhar, Muhammad Malik (Universitas Mataram, 2025)
Background: Fermented feed is the utilization of organic vegetable waste which is then processed together with other supporting components, namely molasses and EM4. Fermentation that occurs in feed here is the process of anaerobic enzymatic changes derived from complex organic compounds into simpler organic products. Thus, the fermented feed processing must be allowed to stand for 3 days before it can be given to livestock, especially chickens. Objective: This work program aims for a strategic solution in reducing environmental pollution caused by the accumulation of harvested vegetable waste and vegetable waste generated from household waste. Methods: The implementation of this activity is carried out by means of Participatory Rural Appraisal (PRA) through the Community Empowerment Real Work Lecture (KKN-PMM) program to farmer groups and breeder groups in order to improve independent food security. Results: Kalikuning Village community members, especially farmer groups and breeder groups, gained knowledge because there was a transfer of knowledge provided from the UNSOED KKN-PMM Team to residents related to the objectives, benefits, and direct practice for making fermented feed.